The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/hrm.21860
|View full text |Cite
|
Sign up to set email alerts
|

The phenomenon of young talent management in Russia—A context‐embedded analysis

Abstract: This article describes the particularities of young talent management (TM) in Russia and explains them through a context‐specific analysis. It adopts a multilevel perspective that acknowledges the relevance of context at three levels: the macro environment, the organizational, and the individual. Data were gathered through 46 interviews with HR managers and young talents from six Russian companies and six Russian subsidiaries of foreign multinational companies (MNCs) active in a variety of industries. Followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 58 publications
0
34
0
1
Order By: Relevance
“…With respect to structuring the contents found in the material, we analysed the data by referring to the definition of GTM and practices used by organisations to attract, select, develop and retain talents in top global positions (Stahl et al, 2007(Stahl et al, , 2012Vaiman et al, 2012;Al Ariss et al, 2014;Al Ariss and Sidani, 2016). Methodologically, all data were examined based on the three-step process provided by Gioia et al (2013), which helps to ensure the much-needed rigour (Thunnissen and Gallardo-Gallardo, 2019) in empirical research into the complex field of TM, as shown in prior studies (Muratbekova-Touron et al, 2018;Festing, 2019, 2020). The data were coded using the software package NVivo 11.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to structuring the contents found in the material, we analysed the data by referring to the definition of GTM and practices used by organisations to attract, select, develop and retain talents in top global positions (Stahl et al, 2007(Stahl et al, , 2012Vaiman et al, 2012;Al Ariss et al, 2014;Al Ariss and Sidani, 2016). Methodologically, all data were examined based on the three-step process provided by Gioia et al (2013), which helps to ensure the much-needed rigour (Thunnissen and Gallardo-Gallardo, 2019) in empirical research into the complex field of TM, as shown in prior studies (Muratbekova-Touron et al, 2018;Festing, 2019, 2020). The data were coded using the software package NVivo 11.…”
Section: Methodsmentioning
confidence: 99%
“…Based on these theoretical insights and the explorative study of a TM programme at one MNC, using several data collection methods and the Gioia et al . (2013) approach for data analysis, which has proven to provide much‐needed rigour (Thunnissen and Gallardo‐Gallardo, 2019) in qualitative empirical research of the complex field of TM (Muratbekova‐Touron et al ., 2018; Harsch and Festing, 2019, 2020), we provide a theoretically‐grounded, empirically‐based and detailed discussion on talents as an important, identifiable elite community within organisations. As a result, we suggest a framework explaining elite construction through TM, which may guide future research.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the latter issue -low talent quality -is overwhelmingly the result of a flawed education system. According to pertinent literature, there is a serious mismatch between the skills acquired by young talents during their education and the ones required by em-РЖМ 18 (3): 383-410 2020ployers Latukha, 2015;Muratbekova-Touron, Kabalina, Festing, 2018]. Authors also mention a lack of managerial and internationally experienced talents (i.e.…”
Section: Factors and Drivers Of Gtm In Emsmentioning
confidence: 99%
“…Studies particularly stress the need for macro level HR interventions: improving the quality of teaching and learning, schooling and university education, and adopting an appropriate national skills' development plan, with new straightforward policies that would stimulate entrepreneurial development and learning [Horwitz, 2013]. Scholars also identify the need for bi-cultural competences' devel-РЖМ 18 (3): 383-410 2020opment [Furusawa, Brewster, 2015], interfunctional mobility [Muratbekova-Touron, Kabalina, Festing, 2018], and awareness and risk management: for example, firms should consider the risks associated with acculturisation-reacculturisation oscillation among expatriate, repatriate and inpatriate talent [Stokes et al, 2016]. This in turn shows that in order for EMs to build a large reservoir of highly qualified workers and be less dependent on the foreign labor market to supply local organizations with talent, different actors -central/local governments, higher educational institutions, MNCs, and indigenous firms -have to work together at sub-national and national levels to ensure that, at the very least, everyone is pulling in the same direction when it comes to human capital development.…”
Section: Key Elements and Outcomes Of Gtm In Em Organizationsmentioning
confidence: 99%
See 1 more Smart Citation